Impact of technology- and parent-based psychosocial interventions on family dynamics factors in children with cancer: A systematic review - Yilin Zhang; Zitong Zhang; Yunyun Peng; Wanting Zhang; Guiyuan Ma; Sulan Lin; Carmen W.H. Chan; Ankie Tan Cheung; Jianhui Xie; Can Gu (PLoS ONE, 2025)
Objective This systematic review aimed to examine the impact of technology- and parent-based psychosocial interventions on family factors among children with cancer, focusing on family dynamics. Methods Data were sourced from ten databases (CNKI, Wanfang, VIP, Sinomed, the Cochrane Library, Embase, PubMed, Web of Science, Scopus, and CINAHL) up to August 2024. The PRISMA statement guidelines, the Cochrane risk bias assessment tool, and the non-randomized controlled trial risk bias assessment tool were used in this study and experimental and quasi-experimental studies were included. The review protocol is registered in PROSPERO (CRD42023435402). Results Twelve studies, including seven randomized controlled trials and five quasi-experimental studies, involving 1,309 parents of children with cancer, were included in the review. These studies utilized various theoretical models and delivered interventions through different modes, such as Internet-based platforms and telehealth. Overall, technology- and parent-based interventions have demonstrated positive effects on family dynamics factors, including family function, communication, coping ability, and family burden. Conclusions Technology- and parent-based psychosocial interventions showed promise in enhancing family dynamics factors although intervention methods varied across studies. This review recommends larger-scale randomized controlled trials to evaluate the effectiveness of technology- and parent-based psychosocial interventions on family dynamics factors among this vulnerable population and highlights the potential of such interventions to improve care quality, treatment outcomes, and resource allocation in pediatric oncology.